2019
DOI: 10.1111/gcbb.12640
|View full text |Cite|
|
Sign up to set email alerts
|

Methane yield and species diversity dynamics of perennial wild plant mixtures established alone, under cover crop maize (Zea mays L.), and after spring barley (Hordeum vulgare L.)

Abstract: The cultivation of perennial wild plant mixtures (WPMs) in biogas cropping systems dominated by maize (Zea mays L.) restores numerous ecosystem functions and improves both spatial and temporal agrobiodiversity. In addition, the colorful appearance of WPM can help enhance landscape beauty. However, their methane yield per hectare (MYH) varies greatly and amounts to only about 50% that of maize. This study aimed at decreasing MYH variability and increasing accumulated MYH of WPM by optimizing the establishment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…Moreover, methods of sowing cup plant under maize were developed . The intercropping of cup plant and maize during the first year of the cup plant establishment also promises to improve environmental performance of maize cultivation through decreased erosion and nutrient leaching …”
Section: Prospective Future Changes At Ephmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, methods of sowing cup plant under maize were developed . The intercropping of cup plant and maize during the first year of the cup plant establishment also promises to improve environmental performance of maize cultivation through decreased erosion and nutrient leaching …”
Section: Prospective Future Changes At Ephmentioning
confidence: 99%
“…The most crucial property of the cup plant as a biogas plant substrate is its specific methane yield (SMY) . Studies have shown that cup plant has a SMY of 0.232–0.275 m N 3 kg −1 volatile solids −1 , which is lower than maize . It should be noted that pretreating similar substrates can increase their biogas yield and will also positively impact processing in the fermenter .…”
Section: Prospective Future Changes At Ephmentioning
confidence: 99%
See 3 more Smart Citations